Acute exercise and high-glucose ingestion elicit dynamic and individualized responses in systemic markers of redox homeostasis - Thomas, Hannah J.; Ang, Teddy; Morrison, Dale J.; Keske, Michelle A.; Parker, Lewan (Frontiers in Immunology, 2023)
Background. Biomarkers of oxidation-reduction (redox) homeostasis are commonly measured in human blood to assess whether certain stimuli (e.g., high-glucose ingestion or acute exercise) lead to a state of oxidative distress (detrimental to health) or oxidative eustress (beneficial to health). Emerging research indicates that redox responses are likely to be highly individualized, yet few studies report individual responses. Furthermore, the effects of complex redox stimuli (e.g., high-glucose-ingestion after exercise) on redox homeostasis remains unclear. We investigated the effect of acute exercise (oxidative eustress), high-glucose ingestion (oxidative distress), and high-glucose ingestion after exercise (both oxidative eu/distress), on commonly measured redox biomarkers in serum/plasma. Methods. In a randomized crossover fashion, eight healthy men (age: 28 ± 4 years; BMI: 24.5 ± 1.5 kg/m2 [mean ± SD]) completed two separate testing conditions; 1) consumption of a high-glucose mixed-nutrient meal (45% carbohydrate [1.1 g glucose.kg-1], 20% protein, and 35% fat) at rest (control trial), and 2) consumption of the same meal 3 h and 24 h after 1 h of moderate-intensity cycling exercise (exercise trial). Plasma and serum were analyzed for an array of commonly studied redox biomarkers. Results. Oxidative stress and antioxidant defense markers (hydrogen peroxide, 8-isoprostanes, catalase, superoxide dismutase, and nitrate levels) increased immediately after exercise (p < 0.05), whereas nitric oxide activity and thiobarbituric acid reactive substances (TBARS) remained similar to baseline (p > 0.118). Nitric oxide activity and nitrate levels decreased at 3 h post-exercise compared to pre-exercise baseline levels. Depending on when the high-glucose mixed nutrient meal was ingested and the postprandial timepoint investigated, oxidative stress and antioxidant defense biomarkers either increased (hydrogen peroxide, TBARS, and superoxide dismutase), decreased (hydrogen peroxide, 8-isoprostanes, superoxide dismutase, nitric oxide activity, nitrate, and nitrite), or remained similar to pre-meal baseline levels (hydrogen peroxide, 8-isoprostanes, TBARS, catalase, superoxide dismutase and nitrite). Redox responses exhibited large inter-individual variability in the magnitude and/or direction of responses. Conclusion. Findings highlight the necessity to interpret redox biomarkers in the context of the individual, biomarker measured, and stimuli observed. Individual redox responsiveness may be of physiological relevance and should be explored as a potential means to inform personalized redox intervention.